2018
DOI: 10.1002/bmc.4384
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐performance liquid chromatography tandem mass spectrometry for the rapid, simultaneous analysis of ziprasidone and its impurities

Abstract: The separation and characterization of the unknown degradation product of second-generation antipsychotic drug ziprasidone are essential for defining the genotoxic potential of the compound. The aim of this study was to develop a simple UHPLC method coupled with tandem mass spectrometry (MS/MS) for chemical characterization of an unknown degradant, and the separation and quantification of ziprasidone and its five main impurities (I-V) in the raw material and pharmaceuticals. Chromatographic conditions were opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The obtained selectivity between ziprasidone and oxy-ziprasidone was improved by the developed method (α = 1.85) compared to UHPLC-DAD analysis (α = 1.12) in ref. [12]. In the case of the separation of aripiprazole and aripiprazole N-oxide, progress was also made compared to the HPLC analysis in ref.…”
Section: Selectivity Performancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained selectivity between ziprasidone and oxy-ziprasidone was improved by the developed method (α = 1.85) compared to UHPLC-DAD analysis (α = 1.12) in ref. [12]. In the case of the separation of aripiprazole and aripiprazole N-oxide, progress was also made compared to the HPLC analysis in ref.…”
Section: Selectivity Performancesmentioning
confidence: 99%
“…The 4arylpiperazines such as aripiprazole and ziprasidone belong to atypical antipsychotics which are among the most effective drugs used in psychiatry in the therapy of schizophrenia, mania, or acute psychotic reactions [4][5]. Literature survey revealed that quanti cation of ziprasidone has been performed by spectrophotometry [6], thin layer chromatography (TLC) [7][8], capillary electrophoresis [9], and high-performance liquid chromatography (HPLC) [10][11][12][13]. The levels of aripiprazole and its main metabolite dehydroaripiprazole were measured using HPLC with UV detection [14][15], capillary-electrophoresis [16], ultraperformance liquid chromatography (UPLC), or gas chromatography coupled with mass spectrometry (GC-MS) [17][18].…”
Section: Introductionmentioning
confidence: 99%
“…MS является оптимальным методом для оценки метаболических трансформаций АП [46] и их влияния на определенные органы и ткани [47], определения концентрации АП в плазме крови [48] не только для клинической практики, но и в отношении случаев токсикологического анализа post mortem [49].…”
Section: изучение механизмов патогенеза шизофрении методами Msunclassified
“…However, the separation was performed with a mobile phase consisting of acetonitrile and buffer (aqueous KH 2 PO 4 solution with triethylamine). The same group developed the highly sensitive UHPLC-MS/MS gradient elution method for the simultaneous quantification of ZPS and its five impurities and with the possibility to characterize the unknown degradation product [ 8 ]. Finally, they have also published a comparative study of the performance of the UHPLC-MS /MS and HPLC-UV methods for the analysis of ZPS and its major impurities [ 9 ].…”
Section: Introductionmentioning
confidence: 99%